Preparation, Characterization and Properties of Cellulose Diacetate/ Poly(caprolactone)diol Graft Copolymer - Guo, Ming; Meng, Hui-Wei; Wang, Peng; Wang, Chun-Peng; Chu, Fu-Xiang (Asian Journal of Chemistry, 2010)
Graft copolymer of poly(caprolactone)diol (PCL) and cellulose diacetate (CDA) was successfully synthesized by two-step reactions. The isocyanate-terminated precursor (NCOPCL) was firstly prepared, and then the NCOPCL was grafted onto cellulose diacetate. The graft copolymer was characterized by FT-infrared spectroscopy, 1H NMR, 13C NMR, SEM and DSC. The results showed that PCL was connected to CDA by chemical bonding and the properties of CDA-g-PCL were changed along with the structure. The possible synthetic mechanism for the reaction of PCL graft with CDA was also suggested preliminarily.